Régimen de protección y conservación del patrimonio arquitectónico en la República Argentina. Criterios de tutela en la Ciudad Autónoma de Buenos Aires - Basile, Silvana Daniela (2020)
The problem of heritage an indispensable instrument of knowledge and its protection are increasingly importance in the contemporary debate as an identity testimony of ways of life and cultures, this aware that it is not possible in architecture to guarantee knowledge of the culture of the past if it is not conserving the matter that testifies it.The following article addresses the issue of the regime of protection and conservation of architectural heritage in the Argentine Republic with the aim of analyzing the development of protection instruments (heritage policies) at the national level, Argentina, and mainly at the local level of the Autonomous City of Buenos Aires. It makes a preliminary analysis of the state of existing legislation from the first preservation regulations to those currently in force. It analyze its development and its limits, by tracing the history of the tools adopted and evaluate the effectiveness of the technical specifications that, although referred to the Argentinian situation, acquire universal significance.